Silver(I)-Catalyzed Oxidation of L-Leucine by Cerium(IV) in Sulfuric Acid Medium: A Kinetic and Mechanistic Study - Sumathi, T.; Shanmugasundaram, P.; Chandramohan, G. (Asian Journal of Chemistry, 2011)
The kinetics of the Ag(I) catalyzed oxidation of L-leucine by cerium(IV) in H2SO4 medium has been investigated at 323 K. The reaction was first order with respect to L-leucine, inverse order with respect to Ce(IV) and a positive fractional order with respect to Ag(I). Increase in [H+] decreased the reaction rate. The added SO42- and HSO4– decreased the rate of the reaction. Under the experimental conditions, the kinetically active species of cerium has been found to be Ce(SO4)2. The major oxidation product of L-leucine has been identified as pentanaldehyde which is confirmed by the IR spectrum. Effects of bivalent and trivalent catalyst have also been studied. Under nitrogen atmosphere, the reaction system can initiate the polymerization of acrylonitrile, indicating the generation of free radicals. A suitable mechanism involving the formation of an intermediate complex with silver catalyst has been proposed.